PERAN SERTA PELAJAR DALAM PENEGAKAN HAK ASASI MANUSIA ATAS LINGKUNGAN HIDUP YANG BAIK DAN SEHAT DI SMA NEGERI I BAJUIN - Nurul Listiyani; Ningrum Ambarsari (Universitas Islam kalimantan MAB, 2018)
Based on the situation analysis and the inventory problems, the main purpose of this Public Service is to increase the students’ legal awareness in order that the students are aware of their right on a good and healthy environment, and able to understand the importance of their participation as a form of the right and obligations in taking care of the living environment in order to stay sustainable.Remembering about the pollution and damage of living environment which is happening in Indonesia, especially in Kecamatan Bajuin, Tanah Laut, then this Public Service activity is expected will decrease the occurrence of the pollution and damage of living environment, by the increasing of the students’ awareness towards their right on a good and healthy environment. By using draft action, it is expected that this public service will be able to produce the students’ legal awareness towards their right on a good and healthy environment which is every citizen’s constitutional rights, so that the students will be active in participating as Indonesian citizen in performing their obligations to take care, conserve, and protect the living environment.